Nanocarrier-based topical drug delivery for an antifungal drug. (April 2014) - Hussain, Afzal; Samad, Abdus; Nazish, Iram; Ahmed, Farhan Jalees
Abstract Objective: The conventional liposomal amphotericin B causes many unwanted side effects like blood disorder, nephrotoxicity, dose-dependent side effects, highly variable oral absorption and formulation-related instability. The objective of the present investigation was to develop cost-effective nanoemulsion as nanocarreir for enhanced and sustained delivery of amphotericin B into the skin. Methods and characterizations: Different oil-in-water nanoemulsions were developed by varying the composition of hydrophilic (Tween® 80) surfactants and co-surfactant by the spontaneous titration method. The developed formulation were characterized, optimized, evaluated and compared for the skin permeation with commercial formulation (fungisome 0.01% w/w). Optimized formulations loaded with amphotericin B were screened using varied concentrations of surfactants and co-surfactants as decided by the ternary phase diagram. Results and discussion: The maximum % transmittance obtained were 96.9 ± 1.0%, 95.9 ± 3.0% and 93.7 ± 1.2% for the optimized formulations F-I, F-III and F-VI, respectively. These optimized nanoemulsions were subjected to thermodynamic stability study to get the most stable nanoemulsions (F-I). The results of the particle size and zeta potential value were found to be 67.32 ± 0.8 nm and –3.7 ± 1.2 mV for the final optimized nanoemulsion F-I supporting transparency and stable nanoemulsion for better skin permeation. The steady state transdermal flux for the formulations was observed between 5.89 ± 2.06 and 18.02 ± 4.3 µg/cm2/h whereas the maximum enhancement ratio were found 1.85- and 3.0-fold higher than fungisome and drug solution, respectively, for F-I. The results of the skin deposition study suggests that 231.37 ± 3.6 µg/cm2 drug deposited from optimized nanoemulsion F-I and 2.11-fold higher enhancement ratio as compared to fungisome. Optimized surfactants and co-surfactant combination-mediated transport of the drug through the skin was also tried and the results were shown to have facilitated drug permeation and skin perturbation (SEM). Conclusion: The combined results suggested that amphotericin B nanoemulsion could be a better option for localized topical drug delivery and have greater potential as an effective, efficient and safe approach.